Penerapan Preference Selection Index (PSI) Dalam Sistem Pendukung Keputusan Pengangkatan Supervisor Housekeeping - Rikky Panggabean; Nelly Astuti Hasibuan (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
Hotels are services that are managed commercially in order to provide lodging facilities to the general public. Grand Antares Hotel is a 4 (four) star hotel or "The Best Four Star Hotel in Medan" whose existence describes it as a resting place. Hotel Grand Antares started operation on February 10, 2008 which has a hotel room capacity of 143 rooms. To provide good service to guests, the hotel has several departments that have duties and responsibilities for each department. One of the departments in the hotel is the housekeeping department, where the duties and responsibilities of the housekeeping department are the cleanliness of the entire public area of ??the hotel. At Hotel Grand Antares, housekeeping supervisors are part of the company's management who play an important role in increasing productivity. Being a housekeeping supervisor means occupying a position that demands responsibility and is hard and challenging. Supervisors must be responsible for other people's work and for their own work. Supervisors must solve problems, make decisions, and act